Implementasi Model KEMP dalam Meningkatkan Minat Efektifitas Pembelajaran PAI di Kelas X A SMAN 1 Sindangbarang - Nugraha, Mulyawan Safwandy; Dedih, Ujang; Mu’min, Wandi Syahrul (TSAQOFAH, 2024)
PAI subjects are identified with learning that is rote, passive and only oriented towards textbooks. This is strengthened by the role of PAI teachers who teach without a mature model and rely on their habits as giving advice in teaching. Learning is one-way and mostly filled with lectures from the teacher. The aim of the research is to design a design based on the Kemp model of PAI competencies. This research uses a qualitative approach as a framework, benchmark and principle, and the research method is content study by utilizing a set of procedures to draw correct conclusions from various book and document sources. The result of the writing is a PAI learning design using the Kemp model which consists of nine elements, starting from a statement of general objectives and ending with an evaluation of learning outcomes. PAI learning will be more meaningful if PAI teachers are willing to implement the Kemp model. The implications of this writing need to be followed up with a field practice study to determine the effectiveness and efficiency of the Kemp model of instructional design.